Evaluation and prediction of infiltration in an Andosol under different land uses - Béjar Pulido, Silvia Janeth; Silva, Israel Cantú; Yánez Díaz, María Inés; Robles, Erik Orlando Luna (Revista Mexicana de Ciencias Agrícolas, 2021)
Infiltration is an indicator of the ability of the soil to retain or drain water, it is influenced by the vegetation cover and type of soil, which when altered modifies its attributes. The objective of the research was to evaluate the behavior of infiltration in an Andosol. Plots of 100 m2 were established, in four areas under two land uses: a forest area and three agricultural areas [two plots of avocado cultivation (under organic and conventional management) and one more plot of macadamia with organic management], the reference year of the research was 2018. In situ infiltration was determined by means of the double-ring method by taking readings for a period of 150 minutes with variable recharges. The parameters of three empirical models were obtained to estimate infiltration: Horton, Kostiakov and Mezencev. Forest use presented the highest initial, final, basic and accumulated infiltration observed with values of 1 880, 863.47, 885.92 mm h-1 and 2 793.29 mm, while the avocado plot with conventional management showed the lowest values with 620, 248.27, 254.83 mm h-1 and 872.49 mm, respectively. The results of the fit of the models showed that Kostiakov’s model better predicts the infiltration process, this according to the values of NSE, r, MAE and R2. Changes from forest use to agricultural uses cause changes in the hydrological variables of the soil resource. Infiltration presented higher rates of speed under organic than conventional management.